2015
DOI: 10.1017/s0029665115002074
|View full text |Cite
|
Sign up to set email alerts
|

Food preferences and underlying mechanisms after bariatric surgery

Abstract: Bariatric surgery leads to significant long-term weight loss, particularly Roux-en-Y gastric bypass (RYGB). The mechanisms underlying weight loss have not been fully uncovered. The aim of this review is to explore the changes in food preferences, as a novel mechanism contributing to weight loss, and also focus on the underlying processes modulating eating behaviour after bariatric surgery. Patients after gastric bypass are less hungry and prefer healthier food options. They develop an increased acuity to sweet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 74 publications
2
51
0
2
Order By: Relevance
“…A profound change in the spontaneous eating habits leading to healthier food options usually occurs after bariatric surgery. Consistent with the neurovulnerability hypothesis, fMRI studies before and after surgery have revealed a reduction in activation of the "emotional brain" after weight loss (8). To further assess the impact of bariatric surgery on appetitive value of foods, Carel le Roux and his colleagues from the Imperial College of London (UK) have submitted fasted lean and obese volunteers to a reward protocol that consisted of clicking 10 times on a computer mouse to obtain a chocolate candy or vegetable pieces, the number of clicks being twofold increased after each reward.…”
Section: A Obesity Is Associated With a Neurovulnerability Of The "Ementioning
confidence: 56%
“…A profound change in the spontaneous eating habits leading to healthier food options usually occurs after bariatric surgery. Consistent with the neurovulnerability hypothesis, fMRI studies before and after surgery have revealed a reduction in activation of the "emotional brain" after weight loss (8). To further assess the impact of bariatric surgery on appetitive value of foods, Carel le Roux and his colleagues from the Imperial College of London (UK) have submitted fasted lean and obese volunteers to a reward protocol that consisted of clicking 10 times on a computer mouse to obtain a chocolate candy or vegetable pieces, the number of clicks being twofold increased after each reward.…”
Section: A Obesity Is Associated With a Neurovulnerability Of The "Ementioning
confidence: 56%
“…In fact, rats with free access to HFD display impaired acquisition of cocaine self-administration (Wellman et al, 2007) and amphetamine-conditioned place preference (Davis et al, 2008). Thus, one may suppose that the reduced consumption of fatty foods following the surgery (Behary and Miras, 2015) may reverse blunted reward and drug seeking. Recent brain imaging studies suggest that following RYGB, food-cues may elicit reduced activation in brain (Ochner et al, 2011; Ochner et al, 2012a; Ochner et al, 2012b; Scholtz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this study, an additional study that measured brain-glucose metabolism indicated activation of brain areas involved in reward expectation and sensory processing during anticipation of a palatable fatty food (Thanos et al 2015). Thus, it appears that while the surgery ultimately reduces intake of rich (very sweet and fatty) foods, an effect reliably demonstrated both in humans and animals (Behary & Miras 2015; Brown et al 1982; Halmi et al 1981; Le Roux et al 2011; Olbers et al 2006), the brain areas activating anticipatory responses to rewarding cues remain on ‘high alert’. In fact, recent studies investigating taste functions and taste reward supports this notion, and suggests that reduced sweet and fat preferences following RYGB surgery are rather due to learned aversions to certain foods, than a primarily reduced reward function (Mathes et al 2015a; Mathes et al 2015b; Mathes et al 2012).…”
Section: Bariatric Surgery As a Risk For Audmentioning
confidence: 97%